Meta Analisis Pengaruh Integrasi Pendekatan STEM Dalam Pembelajaran IPA Terhadap Kemampuan Berpikir Kritis Peserta Didik - Ananda, Prima Nora; Salamah, Ummi (Universitas Negeri Padang, 2021)
This study aims to determine the effect of integrated STEM approach on student’s critical thinking skills in Physics and Science learning. This type of research is a meta-analysis. Meta analysis is a research conducted by summarizing, reviewing and analyzing data from several studies that have been conducted. The research sample consisted of 25 articles that already have an ISSN consisting of 13 international articles and 12 national articles. The data analysis technique used in this study was to calculate the effect size of each article. Based on the results of the study, it was found that the effect of the application of the integrated STEM approach on students' critical thinking skills can be concluded. First, the application of the integrated STEM approach based model has a siginificant effect on the Problem Based Learning model with an average effect 0,92. Second, the application application of integrated STEM has a significant effect on the high school level compared to the junior high school level and elementary school level with an average effect of 1,08. Third, the application application of integrated STEM has a significant effect on the work and force with an average effect 2,23